2020
DOI: 10.1097/mcg.0000000000001450
|View full text |Cite
|
Sign up to set email alerts
|

Combined PEG3350 Plus Lactulose Results in Early Resolution of Hepatic Encephalopathy and Improved 28-Day Survival in Acute-on-Chronic Liver Failure

Abstract: Background and Aims: Acute-on-chronic liver failure (ACLF) is associated with high short-term mortality in those with hepatic encephalopathy (HE). Polyethylene glycol (PEG) 3350 electrolyte solution can ensure rapid gut catharsis, which may resolve HE more effectively than lactulose. In this open-label-randomized trial, we compared PEG+lactulose versus lactulose alone in ACLF with HE grade ≥ 2 for efficacy and outcome.Patients and Methods: Patients were randomized to receive PEG (2 L q12 h) followed by lactulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Naderian et al 21 found that patients treated with PEG and lactulose had a shorter mean hospital stay of 6.8 days compared with patients treated with lactulose alone (mean 8.9 days). These results were also validated by Ahmed et al 22 who found that patients treated with both PEG and lactulose had a mean hospital stay of 9 days compared with 13 days in patients treated with lactulose alone. However, despite the fact that the studies included in this analyses [8][9][10][11] commented on the shorter length of hospital stay in patient receiving PEG, our analysis failed to show statistical significance in terms of length of hospital stay even after omitting one study to create a more homogenous group.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Naderian et al 21 found that patients treated with PEG and lactulose had a shorter mean hospital stay of 6.8 days compared with patients treated with lactulose alone (mean 8.9 days). These results were also validated by Ahmed et al 22 who found that patients treated with both PEG and lactulose had a mean hospital stay of 9 days compared with 13 days in patients treated with lactulose alone. However, despite the fact that the studies included in this analyses [8][9][10][11] commented on the shorter length of hospital stay in patient receiving PEG, our analysis failed to show statistical significance in terms of length of hospital stay even after omitting one study to create a more homogenous group.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, a significantly higher proportion of patients in the PEG group had a reduction of HESA Score by ≥1 grade at 24 hours post treatment compared with lactulose and a significantly higher proportion of patients in the PEG group had HESA Score of grade 0 at 24 hours. In fact, two studies by Naderian et al 21 and Ahmed et al 22 compared the concomitant use of PEG with lactulose versus lactulose and concluded that the combination had led to a higher 24 hours HESA Score change as well as a higher reduction in HESA Score by more than one grade at 24 hours post treatment. The mechanism by which PEG improved HESA Score remains debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies with a total of 148 patients compared PEG (n=73) with lactulose (n=75) in the levels of serum ammonia concentration. 10 , 11 , 14 The results showed that the ammonia concentration of the baseline was consistent (WMD=6.851, 95% CI: −2.72 to 16.424; P =0.161; Supplementary File 5: Figs. S5A, S5B, Supplemental Digital Content 1, http://links.lww.com/JCG/A784 ) with insignificant heterogeneity (χ 2 =3.09, P =0.214, I 2 =35.2%).…”
Section: Resultsmentioning
confidence: 89%
“…Since PEG is a highly effective laxative, the potential clinical improvement of HE may be more clinically significant than the actual decline in ammonia levels. 10 Publication bias and sensitivity analysis were not conducted due to only 3 studies include in the analysis. As such, this conclusion should be explained with caution and require more high-quality, multicenter RCTs validation.…”
Section: Discussionmentioning
confidence: 99%
“…Two Indian randomized control trials reported significant improvement of HESA score in the PEG group when compared to lactulose. 86,87 Currently, two trials are under process to access the therapeutic use of PEG in HE. 88,89 Nitazoxanide Nitazoxanide (NTZ) is a broad-spectrum thiazolide antiparasitic agent which has action against many anaerobic bacteria, protozoa, and helminthic species.…”
Section: Polyethylene Glycolmentioning
confidence: 99%